2021
DOI: 10.3390/molecules26072103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Squid (Dosidicus giga) Mantle Protein with a Mixtures of Potato and Corn Starch in an Extruded Snack, as Characterized by FTIR and DSC

Abstract: The majority of snacks expanded by extrusion (SEE) are made with vegetable sources, to improve their nutritional content; it has been proposed to incorporate squid (Dosidicus gigas), due to its high protein content, low price and high availability. However, the interaction of proteins of animal origin with starch during extrusion causes negative effects on the sensory properties of SEE, so it is necessary to know the type of protein–carbohydrate interactions and their effect on these properties. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Moreover, the absorption at 995 cm −1 is correlated with the crystallization region (van Soest et al, 1995 ). Some studies have shown that branched starch chains interact with each other to form a lattice structure, linking the double helix structure and forming a crystalline region, while straight‐chain starches form an amorphous region (Valenzuela‐Lagarda et al, 2021 ). According to the infrared spectrum, the ratios of absorption peak intensity at 995 cm −1 /1022 cm −1 of KS, A‐KRS, DA‐KRS, and PA‐KRS were 1.031, 1.003, 0.998, and 0.974.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the absorption at 995 cm −1 is correlated with the crystallization region (van Soest et al, 1995 ). Some studies have shown that branched starch chains interact with each other to form a lattice structure, linking the double helix structure and forming a crystalline region, while straight‐chain starches form an amorphous region (Valenzuela‐Lagarda et al, 2021 ). According to the infrared spectrum, the ratios of absorption peak intensity at 995 cm −1 /1022 cm −1 of KS, A‐KRS, DA‐KRS, and PA‐KRS were 1.031, 1.003, 0.998, and 0.974.…”
Section: Resultsmentioning
confidence: 99%
“…−1 is correlated with the crystallization region (van Soestet al, 1995). Some studies have shown that branched starch chains interact with each other to form a lattice structure, linking the double helix structure and forming a crystalline region, while straight-chain starches form an amorphous region(Valenzuela-Lagarda et al, 2021).…”
mentioning
confidence: 99%
“…Food extrusion is a process of several unit operations as thermal and mechanical treatment by which protein and/or starch-rich ingredients are fed into an extruder barrel through the feed hopper and the screw then conveys the food by compression, mixing, shearing, kneading and high temperature to produce a variety of products [2]. Several studies have shown that is possible to develop extruded snacks with pseudocereals such as quinoa to improve their antioxidant properties and with jumbo squid mantle, due to its high protein content, low price, and high availability [3][4][5]. Canihua, (Chenopodium pallidicaule Aellen), is a nutritious grain from the South American Andean highlands, cultivated in Puno, Peru, between 3200 and 4200 amsl.…”
Section: Introductionmentioning
confidence: 99%